Psychological mechanisms and configurational pathways of participation in personal transportation carbon trading: an environment–cognition–intention perspective - Wu, Xiaohui; Zhao, Jiani; Li, Shuzhen; Cao, Shuchao; Shi, Yuji; He, Meiling (Frontiers in Psychology, 2025)
IntroductionPersonal transportation carbon emissions pose a key challenge to environmental sustainability, and establishing a personal transportation carbon trading market can help promote the overall low-carbon transformation of society. However, its effectiveness is still constrained by insufficient public participation and a limited understanding of the psychological mechanisms and configurational pathways underlying participation intention.MethodsThis study is based on Social Cognitive Theory (SCT) and explores the key factors influencing residents’ participation intention, as well as the internal connections between these factors, from an Environment–Cognition–Intention perspective. The psychological response mechanisms of individuals’ cognition and intention under external environmental stimuli were examined using structural equation modeling (SEM), and fuzzy set qualitative comparative analysis (fsQCA) was applied to identify configurational pathways that lead to participation intention.ResultsThe results indicate that environmental factors, including policy formulation (PF), social support and social norms (SSN), positively influence participation intention (PI). This influence not only directly affects PI but also operates through a series of interrelated cognitive processes, including self-efficacy (SE), perceived usefulness (PU) and perceived ease of use (PEOU), which in turn enhance PI. However, perceived risk (PR) acts as a negative cognitive factor suppressing PI. Furthermore, configurational analysis also clearly demonstrates multiple causal pathways leading to high PI, highlighting that combinations of strong social support and norms, high PU, and low PR are particularly effective.DiscussionThis study provides deeper insight into the psychological mechanisms underlying low-carbon behavior, highlighting how the market activates motivation through economic incentives and reinforces the influence of social norms and perceived collective responsibility on individual behavior. Configurational pathways further suggest that specific combinations of social and cognitive conditions can foster high PI. It provides theoretical support for the development of targeted behavioral incentive strategies to enhance public participation in personal transportation carbon trading and thereby promote environmental sustainability.